Critical component wear in heavy duty engines - Lakshminarayanan, P. A. (Wiley, 2011)
The critical parts of a heavy duty engine are theoretically designed for infinite life without mechanical fatigue failure. Yet the life of an engine is in reality determined by wear of the critical parts. Even if an engine is designed and built to have normal wear life, abnormal wear takes place either due to special working conditions or increased loading.℗¡ Understanding abnormal and normal wear enables the engineer to control the external conditions leading to premature wear, or to design the critical parts that have longer wear life and hence lower costs. The literature on wear phenomenon r.